2018
DOI: 10.1177/1550059418780780
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal EEG Power Spectra in Acute Transient Global Amnesia: A Quantitative EEG Study

Abstract: Transient global amnesia (TGA) is a clinical syndrome characterized by retrograde and anterograde amnesia without other neurological deficits. Although electroencephalography (EEG) methods are commonly used in both clinical and research setting with TGA patients, few studies have investigated neurophysiological pattern in TGA using quantitative EEG (qEEG). The main aim of the present study was to extend these previous findings by exploring EEG power spectra differences between patients with acute TGA and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…The patients with TGA and lesions on DWI were further examined using fMRI. Similar to the results of previous studies, 12,16,17,[20][21][22][23][24][25] our findings showed that the lesions on DWI were mainly located in the hippocampal CA1 area (Figure 3). Seven of the patients with TGA and hippocampal lesions on DWI were right-handed, suggesting that the left cerebral hemisphere was dominant.…”
Section: Lesions On Dwisupporting
confidence: 91%
See 1 more Smart Citation
“…The patients with TGA and lesions on DWI were further examined using fMRI. Similar to the results of previous studies, 12,16,17,[20][21][22][23][24][25] our findings showed that the lesions on DWI were mainly located in the hippocampal CA1 area (Figure 3). Seven of the patients with TGA and hippocampal lesions on DWI were right-handed, suggesting that the left cerebral hemisphere was dominant.…”
Section: Lesions On Dwisupporting
confidence: 91%
“…Although several studies have reported an abnormal EEG in patients with TGA, they failed to diagnose epilepsy. 21 , 37 In most studies, the EEG of patients with TGA returns to normal after the patients have recovered from TGA, so the findings are not sufficiently convincing. In our study, eight patients underwent EEG, and their results were normal.…”
Section: Discussionmentioning
confidence: 99%
“…We show one exemplary subject for each condition TEA and TGA, PSA is shown with topographies of instantaneous frequency at each band (delta, theta, alpha, beta, gamma). Moreover, for each condition we show the topography in average beta power (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Spectral activity in the TEA patient is more scattered and beta power topography appears to be more asymmetric compared to TGA patients.…”
Section: Eeg Pipeline Analysismentioning
confidence: 99%
“…According to a recent study, only a small sub-group (about 26%) might show some non-specific acute abnormalities such as bilateral slowing [13]. Other studies on EEG spectral analysis in TGA patients found a diffuse symmetric decrease of beta and theta activity during the acute phase [14]. Meanwhile, there are no quantitative EEG (qEEG) studies describing spectral activity in patients with Transient Epileptic Amnesia.…”
Section: Introductionmentioning
confidence: 98%
“…In TGA patients, a prior qEEG study demonstrated a decrease in absolute theta power in fronto-temporal regions and a decrease in absolute beta power in the parietal lobe during the acute phase [ 16 ], while another work showed a marked reduction of absolute beta 1 and alpha power in the left temporo-parietal regions far from amnesia attack when compared with healthy controls [ 17 ]. More recently, our group demonstrated an increased beta power in the uncus and parahippocampal gyrus of the affected hemisphere of patients with TEA when compared to those affected by TGA [ 18 ].…”
Section: Introductionmentioning
confidence: 99%